Health behaviours in women treated for infertility and their influence on the incidence of depression - Makara-Studzińska, Marta; Morylowska-Topolska, Justyna; Wdowiak, Artur; Urbańska, Anna (Polish Journal of Public Health, 2010)
Introduction. The style of life, the diet, undertaking risky behaviours, such as for instance smoking, drinking alcohol, can significantly influence fertility. Almost 21% of the female population experiences a major depression during their lives. The severity of anxiety and depression in women with infertility problem seems to be comparable with that experienced by women with cancer or coronary disease.Aim. The aim of the study was to analyze the chosen health behaviours in women treated for infertility and to assess the potential impact of these behaviours on the presence of anxiety and depression.Material and methods. The questionnaire comprising questions related to promoting health- and health-adverse behaviours before and during infertility treatment was developed for the purpose of the study. Beck Depression Inventory (BDI) was used to assess the severity of anxiety and depression.Results. Leading an active lifestyle prior to infertility treatment was connected with intensification of that activity comparing to the women who did not lead an active lifestyle in the past. Most of the respondents did not change their dietary habits during infertility treatment. The women who changed their diet significantly increased the consumption of fish, vegetables, dairy products and fruits.Conclusion. Infertility treatment significantly influenced the decision of the studied women about reducing or quitting smoking, as well as reducing the consumption of other stimulants, such as alcohol or coffee.